A função social da posse e da tutela possessória em regiões fronteiriças do Mercosul - Gehrke, Luís Carlos (2008)
This research focus on the social question of possession and of tutelage in a border region of Mercado Comum do Sul (Mercosul), analyzing by a view of civil law as well as of fundamental law, investigating what are the forthcoming about Mercosul countries. It will be investigate if the Mercosul countries protect their possession. The juridical institute and the tutelage effectivity. For this research, at the first moment it will be the historic aspects about the question, analyzing since exist the worry about the question, and after that, the migration as the fact determinant in this process of restriction about the access of possession, and for finish, the tutelage of this possession for the Democratic State of Law. In this point, is development the view of possession and, especially, the social function, thinking about the supremacy as important factor in the interests of the states. For conclude, will be present the actual question of possession, when it is determinant in conflicts, especially in borders without legislation for this areas, analyzing as well by a view of the possession and the borders areas in Brazil, Argentina, Paraguai and Uruguai.